Consuming Leisure Time - Ratna Istriyani (Journal of Contemporary Sociological Issues, 2021)
This article explores the concept of leisure time and its connections to trends in tourism. Examining the specific implications of tourist agendas on previously ‘rural’ villages, this study demonstrates how the tourist agenda has shaped leisure time and contributed to the transformation of places into more commercial, tourist hubs, aiming to maximize consumer attraction. Crucially, new economic features associated with the tourism trade have altered social relations and dynamics in rural areas. These changes can also be seen in Yogyakarta, especially villages in the Sleman area. This study uses qualitative methods to explore the economic changes experienced within the village associated with its formation as a tourist destination, drawing on observational and secondary data sets. Changes in economic patterns, generally, cannot be separated from the tourism trend. In this article, tourism trend refers to consumer market which emphasizing the modification of classical nuances which refers to the proliferation of restaurants and cafes in rural areas at Sleman. This study argues that the tourism trend in rural areas has not only changed their economic complexion but has also highlighted the character of the village as a space for urban community consumption. The economic shift from the expansion of the tourism sector is assumed to be able to contribute to development of rural areas. However, it is not necessarily possible to realize that sustainable regional development demand creativity to compete with the emergence of new entertainment venues. Keywords: Tourism Transformation, Village, Leisure, Space Consumption.